2022
DOI: 10.34133/2022/9892526
|View full text |Cite
|
Sign up to set email alerts
|

Graphdiyne-Related Materials in Biomedical Applications and Their Potential in Peripheral Nerve Tissue Engineering

Abstract: Graphdiyne (GDY) is a new member of the family of carbon-based nanomaterials with hybridized carbon atoms of sp and sp2, including α, β, γ, and (6,6,12)-GDY, which differ in their percentage of acetylene bonds. The unique structure of GDY provides many attractive features, such as uniformly distributed pores, highly π-conjugated structure, high thermal stability, low toxicity, biodegradability, large specific surface area, tunable electrical conductivity, and remarkable thermal conductivity. Therefore, GDY is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 146 publications
(196 reference statements)
0
8
0
Order By: Relevance
“…Li et al (2023) investigated the biocompatibility of graphdiyne and its potential for neural tissue engineering. The study demonstrated that graphdiyne supported the attachment and growth of neural stem cells, suggesting its potential for nerve tissue regeneration [135]. This property is crucial for developing tissue-engineered constructs that can integrate seamlessly with the host tissue.…”
Section: Cell Adhesion and Proliferationmentioning
confidence: 88%
See 1 more Smart Citation
“…Li et al (2023) investigated the biocompatibility of graphdiyne and its potential for neural tissue engineering. The study demonstrated that graphdiyne supported the attachment and growth of neural stem cells, suggesting its potential for nerve tissue regeneration [135]. This property is crucial for developing tissue-engineered constructs that can integrate seamlessly with the host tissue.…”
Section: Cell Adhesion and Proliferationmentioning
confidence: 88%
“…Current Results: Initial studies have demonstrated the biocompatibility and potential of graphdiyne scaffolds for promoting tissue regeneration in bone [132], nerve [133], and cardiac tissues [134]. Graphdiyne's ability to support cell growth and facilitate tissue repair offers promising opportunities in regenerative medicine [135].…”
Section: Graphdiyne In Tissue Engineering and Biomedical Devicesmentioning
confidence: 99%
“…This integration allows for precise identification of the surgical location and direction, minimizing the risk of instrument collisions with nontarget tissues. [ 2,3 ] Guidewires are the most important surgical instruments used in intravascular interventional surgery. The surgeon navigates the delivery tool to the target point by observing the guidewire under real‐time fluoroscopy images.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–4 ] To this end, researchers have made great efforts to develop various nanomaterials with tailored physicochemical properties (such as size, shape, and surface chemistry) and programmed biological functionalities (such as anticancer, antibacterial, and anti‐inflammatory abilities). [ 5–9 ] For example, polymer‐based nanomaterials can be designed to target cancer cells, [ 10 ] infection sites, [ 11 ] and/or inflamed tissues. [ 12 ] Inorganic nanomaterials can be fabricated to target tumor tissue [ 13 ] or infected tissue [ 14 ] and, when irradiated with light, can also generate localized hyperthermia to photothermally eliminate tumors, [ 15 ] bacteria, [ 16 ] bacterial biofilms [ 17 ] (i.e., photothermal therapy), or produce reactive oxygen species (ROS) to destroy cancer cells [ 18,19 ] and bacteria [ 20–22 ] (i.e., photodynamic therapy [PDT]).…”
Section: Introductionmentioning
confidence: 99%